Analisis Internal dan Eksternal Pembangunan Pabrik Pupuk Organik di Kabupaten Jember - Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu; Amam, Amam (Universitas Galuh, 2024)
Livestock businesses generally produce outputs in the form of main results and side products (by-products). By-products in the form of livestock waste generally have not been managed and processed by business actors, even though the management and processing of livestock waste has the potential to improve the community's economy, because livestock waste, in addition to being abundant in quantity, is also continuously produced from livestock businesses. The aim of the research is to examine the internal and external analysis of the construction of an organic fertilizer factory made from livestock manure as raw material. The research location is Sumberjambe District, Jember Regency. The research was conducted using quantitative descriptive methods. Data collection methods use desk research, observation, Focus Group Discussion (FGD), and surveys. This research involved 34 key respondents in efforts to build an organic fertilizer factory. Data analysis uses the IFAS, EFAS and SWOT analysis approaches. The research results showed that internal analysis consisting of strength and weakness factors had a weight of 0.505 and 0.495, while external analysis consisting of opportunity and threat factors had a weight of 0.527 and 0.473. This research concluded that the strategy for building an organic fertilizer factory in Jember Regency uses a strengths and opportunities strategy, namely utilizing internal strengths to seize opportunities.